2017
DOI: 10.1148/radiol.2017162056
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered Radiology: Where Are We, Where Do We Want to Be, and How Do We Get There?

Abstract: Purpose The objectives of the Radiological Society of North America (RSNA) Patient-Centered Radiology Steering Committee survey were to (a) assess RSNA members' general attitudes and experiences concerning patient-centered radiology, with specific attention paid to radiologist-to-patient communication; (b) examine the members' barriers to communicating more directly with patients; and (c) explore their perceptions of how such barriers can be overcome. Materials and Methods A total of 5999 radiologists were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 24 publications
0
30
0
6
Order By: Relevance
“…Debriefing with these advocates after they assist a patient can provide useful insight into where QS efforts should be focused. Beyond seeking to understand patients' experiences, diagnostic radiologists are increasingly interested in more direct interactions with patients (49). Opportunities for this include establishing radiology consultation clinics and directly embedding radiologists into subspecialty clinics where they can meet with patients during their clinical appointments (50)(51)(52).…”
Section: Pitfall: Limited Understanding Of the Patient And Referring mentioning
confidence: 99%
“…Debriefing with these advocates after they assist a patient can provide useful insight into where QS efforts should be focused. Beyond seeking to understand patients' experiences, diagnostic radiologists are increasingly interested in more direct interactions with patients (49). Opportunities for this include establishing radiology consultation clinics and directly embedding radiologists into subspecialty clinics where they can meet with patients during their clinical appointments (50)(51)(52).…”
Section: Pitfall: Limited Understanding Of the Patient And Referring mentioning
confidence: 99%
“…Although referred patients generally arrive with outside imaging studies and interpretations, numerous studies showed that second-opinion subspecialty radiology consultations are clinically valuable and often lead to changes in patient management. [1][2][3][4][5][6][7][8] In fact, discrepancy rates were found to be as high as 26% between radiologists with different levels of specialty training including those trained in MSK imaging. [20][21][22] Although we believe this phenomenon to be true throughout the MSK imaging arena, we have shown the value of subspecialty MSK imaging expertise in the orthopaedic oncology arena.…”
Section: Add Value and Show Valuementioning
confidence: 99%
“…These changes in orthopaedic practices can offer radiologists a primitive road map to navigate with an end point of providing excellent service, quality imaging, and consistent effective communication. 6 Radiology practices are also enlarging in physician numbers, whether in corporate, private practice, academic, or hybrid models. MSK imaging is trending toward increasing subspecialization, with a greater percentage of high-end orthopaedic imaging studies now interpreted by subspecialty fellowship-trained radiologists.…”
mentioning
confidence: 99%
“…Given the importance of patient involvement in the medical care process, the lack of possibilities for patients to talk to the radiologists seems to be detrimental. The radiological associations ACR and RSNA consider this shortcoming a potential threat to the profession and therefore promote a more patient-centered radiology [ 11 , 12 ]. Hence, they launched several counter-acting initiatives and campaigns, such as “Face of Radiology”, “Five Patients per Day”, or “Radiology Cares” to enhance patient-doctor interactions and communication [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%